PERBEDAAN PENGARUH PEMBELAJARAN LOMPAT JAUH TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK PADA SISWI PUTRI KELAS III SEKOLAH DASAR - Mandalawati, Titin Kuntum (Premiere Educandum, 2015)
The purpose of this study was to determine differences in effect learning to use tools long jump rope and circle as high stimulation and distance gradually towards results learn long jump squat style. This study used an experimental method. Experiment by using pre and post test. The study consisted of two groups: tools strap (A) and the group as a circle high stimulation (B). This study population is third grade Elementary School 1 Panggung Barat Magetan 2015. Â The average results of the study group pretest tools strap (A) amounted to 84.1 and group as circle high stimulation 82.4 (B), initial conditions showed two groups with similar capabilities. The average post test group tools strap (A) amounted to 156.8 and the group as a circle high stimulation 151.4 (B). Based on the results obtained the following conclusions there is a significant difference between the long jump learning using 2 tools and circle as high stimulation and distance gradually towards learning outcomes long jump squat style on third grade Elementary School 1 Panggung Barat Magetan 2012/2013. By p (0.034 < 0.05). Long jump teaching methods using tools ropes with better results.Â Keywords: Learning the long jump, long jump squat style